Low‐power and area‐efficient design of AES S‐Box using enhanced transformation method for security application. (7th January 2020) - Nandan, V.; Gowri Shankar Rao, R.
Summary: In implementing well‐known advanced encryption standard (AES) algorithm, the main part for constructing the hardware is S‐Box, which is abbreviated from substitution box. This is the basic component of symmetric key cryptographic algorithm, and it requires in AES because of its nonlinear organization with multiplicative inversion. This S‐Box is designed by two transformations, ie, inversing the multiplication part in Galois field directed with modified affine transformation. The limitation of S‐Box is more time and power consumption. This limitation has to be overcome by doing slight modification in affine and inverse affine transform. The time consumption for AES S‐Box is decreased by the proposed transformation method. The proposed system achieved 39% power when compared with the existing system; the proposed system is efficient. Abstract : This substitution box is designed by two transformations, ie, inversing the multiplication part in Galois field directed with modified affine transformation. The limitation of S‐Box is more time and power consumption and that has to be overcome by doing slight modification in affine and inverse affine transform. The time consumption for AES S‐Box is decreased by the proposed transformation method. The proposed system achieved 39% power when compared with existing system; the proposed system is efficient.